Analisis Manpower Planning Terhadap Kinerja Pelayanan Teknik dengan Metode Workload Analysis (WLA) di PT. PLN (Persero) UP3 Madiun - Muhammad Romadana Syaifullah; Karuniawati Hasanah; Dwi Murniyati (UNIVERSITAS PGRI MADIUN, 2026)
Abstract: The Analysis of Manpower Planning on Engineering Service Performance Using the Workload Analysis Method at PT. PLN (Persero) UP3 Madiun. This study aims to analyze workforce planning (manpower planning) on engineering service performance at PT. PLN (Persero) UP3 Madiun using the Workload Analysis (WLA) method. The approach used was descriptive quantitative, with secondary data collected from technician reports for November 2024. WLA was used to calculate effective working hours, performance ratings, allowances, and average workload and distribution among technician teams. The analysis results showed workload inequality, with Team C experiencing the highest workload with a time utilization rate of 94.13%, while Team D only had 0.30%. This finding indicates an unequal distribution of technician work, potentially reducing service efficiency. Therefore, this study suggests the need to review human resource distribution and implement WLA as a workforce planning tool to improve overall engineering service performance. Keywords: Manpower Planning; Workload Analysis; Engineering Service Performance; PLN; Workload Distribution.